Zoometry and prediction equations for the estimation of body weight in Corriedale ewes - Canaza-Cayo, Ali William (2017)
This study aimed to evaluate the relationship between body weight and body measurements of Corriedale sheep and get through these simple measurements in live animal models to predict weight. It was used 100 animals. There was a high correlation (r> 0.60) of body weight with body measurements, and the abdominal perimeter (PA) which showed greater correlation. It can be predicted body weight using the following equation: PV= -62.057 + 0.452PA + 0.222LoC + 0.557AH + 0.658LC + 0.578AL, resulting in a coefficient of determination of 0.76.